Prevalence of lameness and metabolic disorders in endurance horses - Adamu, Lawan; Mohd Adzahan, Noraniza; Abdullah, Rasedee; Fateh Mohamed, Bashir Ahmad (Department of Veterinary Services Malaysia, 2012)
This study was carried out to investigate the prevalence of equine lameness and metabolic disorders in endurance horses during an endurance race. Out of 67 horses that participated in the race, 19 horses completed the race successfully without any derangement while 48 horses were eliminated from the race for various disorders. Fifty-three (53.73%) percent of these horses had metabolic disorders and 17.91% were eliminated due to lameness. The study showed that the highest number of endurance horses that were eliminated were due to metabolic disorders followed by lameness. These findings may assist veterinarians in designing laudable measures in the management and conditioning protocols of endurance horses during training and further prevent the morbidity and mortality during endurance races.